2015
DOI: 10.1016/j.hrtlng.2014.09.002
|View full text |Cite
|
Sign up to set email alerts
|

COPD is associated with cognitive dysfunction and poor physical fitness in heart failure

Abstract: Objective To examine the associations among chronic obstructive pulmonary disease (COPD), cognitive function, and physical fitness in heart failure (HF). Background Cognitive impairment in HF in part stems from medical comorbidities and poor physical fitness. COPD, a frequent co-existing condition in HF, is a risk factor for cognitive impairment and a known cause of poor physical fitness. Yet, the interplay among COPD, cognition, and physical fitness has never been examined in HF. Methods 191 HF patients c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Such findings were seen in several studies [32][33][34]. Patients with CVD with osteoarthritis comorbidity were found to have poorer physical health [35] and those with chronic obstructive pulmonary disease exhibited poorer physical fitness [36]. Shad et al also reported that the MCS was significantly lower in patients with multiple comorbidities, with the MCS being related to sex and educational level [32].…”
Section: Discussionmentioning
confidence: 80%
“…Such findings were seen in several studies [32][33][34]. Patients with CVD with osteoarthritis comorbidity were found to have poorer physical health [35] and those with chronic obstructive pulmonary disease exhibited poorer physical fitness [36]. Shad et al also reported that the MCS was significantly lower in patients with multiple comorbidities, with the MCS being related to sex and educational level [32].…”
Section: Discussionmentioning
confidence: 80%
“…Cognition was assessed using a neuropsychological battery of four tests used commonly in patients with HF (Alosco, Spitznagel, Josephson, Hughes, & Gunstad, 2015; Miller et al, 2012) that measured attention, processing speed, working memory, and short-term memory. The Digit Symbol Substitution Test (DSST) is a timed test in which numbers are matched with different nonsense symbols.…”
Section: Methodsmentioning
confidence: 99%
“…Slowed processing speed, inability to remember earlier responses, and reduced capacity to ignore irrelevant information all contribute to decrements in performance. The internal consistency coefficient is .82 (Silva, 2008) and test-retest reliability is .75 (Alosco et al, 2015). …”
Section: Methodsmentioning
confidence: 99%
“…30,31 Additionally, the severity of COPD was recorded using the Global Initiative for Chronic Obstructive Lung Disease (GOLD) classification. Balance with the one-leg stance test, [32][33][34] functional capacity with the 2-min step in place, [35][36][37] and fatigue with the Piper fatigue scale [38][39][40] were also assessed due to the association of these measurements with frailty.…”
Section: Measurementsmentioning
confidence: 99%